Instability Analysis of a Low-Angle Low-Expansive Soil Slope under Seasonal Wet-Dry Cycles and River-Level Variations - Yongzheng Qi; Zongzhi Wang; Haoqing Xu; Zirui Yuan (Advances in Civil Engineering)
There were a small amount of obvious offsets at the bearing of bridge piers built on an artificial gentle canal bank terrace and many tensile cracks visible at the surface of the mortar block stones covering the terrace soil in several years following construction. To determine these reasons, a comprehensive site investigation and a wide variety of tests were implemented, which included geophysical tests, in situ tests, laboratory tests, pile integrity detection, and numerical analysis with the finite element method (FEM). The results revealed that the soil of the low-angle slope was the potentially low-expansive clay soil. The reduction in soil shear strength deriving from seasonal wet-dry cycles and river-level variations led to the instability and failure of the low-angle low-expansive soil slope, which triggered the collapses of the soil slope and lots of fractures in the piles of the bridge foundation. The typical characteristics of the instability and failure of the low-angle low-expansive soil slope were tractional detachment and slow sliding.